Mechanism of stress relaxation and phase transformation in additively manufactured Ti-6Al-4V via in situ high temperature XRD and TEM analyses. (15th April 2020) - Kaschel, F.R.; Vijayaraghavan, R.K.; Shmeliov, A.; McCarthy, E.K.; Canavan, M.; McNally, P.J.; Dowling, D.P.; Nicolosi, V.; Celikin, M.
Abstract: Additive manufacturing is being increasingly used in the fabrication of Ti-6Al-4V parts to combine excellent mechanical properties and biocompatibility with high precision. Unfortunately, due to the build-up of thermal residual stresses and the formation of martensitic structure across a wide range of typical processing conditions, it is generally necessary to use a post-thermal treatment to achieve superior mechanical performance. This investigation aims to obtain a deeper understanding of the micro/nanostructural evolution ( α ′ martensite phase decomposition), accounting for the kinetics of phase transformation during the heat treatment of 3D-printed Ti-6Al-4V alloy. As the mechanism of phase transformation and stress relaxation is still ambiguous, in this study the changes in crystal lattice, phase, composition and lattice strain were investigated up to 1000°C using both in situ high temperature X-ray diffraction (XRD) and transmission electron microscopy (TEM). Based on the result a mechanism of phase transformation is proposed, via the accommodation/substitution of Al, V and Ti atoms in the crystal lattice. The proposed mechanism is supported based on elemental concentration changes during heat treatment, in combination with changes in crystal structure observed using the high temperature XRD and TEM measurements. This study provides a deeper understanding on the mechanism of phase transformation through martensitic decomposition, as well as a deeper understanding of the influence of post-thermal treatment conditions on the alloy's crystal structure. Graphical abstract: Image, graphical abstract